Behavioral and Movement Disorders due to Long-Lasting Myoclonic Status Epilepticus Misdiagnosed as ADHD in a Patient With Juvenile Myoclonic Epilepsy: Electroclinical Findings and Related Hemodynamic Changes. (January 2016) - Fanella, Martina; Carnì, Marco; Morano, Alessandra; Albini, Mariarita; Lapenta, Leonardo; Casciato, Sara; Fattouch, Jinane; Di Castro, Elisabetta; Colonnese, Claudio; Vaudano, Anna Elisabetta; Giallonardo, Anna Teresa; Di Bonaventura, Carlo
Epilepsy and attention-deficit/hyperactivity disorder (ADHD) likely share common underlying neural mechanisms, as often suggested by both the evidence of electroencephalography (EEG) abnormalities in ADHD patients without epilepsy and the coexistence of these 2 conditions. The differential diagnosis between epilepsy and ADHD may consequently be challenging. In this report, we describe a patient presenting with a clinical association of "tics" and behavioral disorders that appeared 6 months before our first observation and had previously been interpreted as ADHD. A video-EEG evaluation documented an electroclinical pattern of myoclonic status epilepticus. On the basis of the revised clinical data, the EEG findings, the good response to valproate, the long-lasting myoclonic status epilepticus, and the enduring epileptic abnormalities likely causing behavioral disturbances, the patient's symptoms were interpreted as being the expression of untreated juvenile myoclonic epilepsy. The EEG–functional magnetic resonance imaging study revealed, during clinical generalized spike-and-wave and polyspike-and-wave discharges, positive blood oxygen level–dependent (BOLD) signal changes bilaterally in the thalamus, the prefrontal cortex (Brodmann area 6, supplementary motor area) and the cerebellum, and negative BOLD signal changes in the regions of the default mode network. Such findings, which are typical of BOLD changes observed in idiopathic generalized epilepsy, may also shed light on the anatomofunctional network underlying ADHD.